Coffea: The Application of green Components in Cosmetics Formulation - Liza Pratiwi (Faculty of Pharmacy, Universitas Gadjah Mada, 2021)
In recent years, the use of green components has attracted significant attention because of their safety, various pharmacological effects, various possible formulation applications, and renewable sources. Regarding its development, coffee is a potential candidate for alternatives of synthetic chemicals in cosmetic preparations because it contains active compounds including polyphenols, caffeine, chlorogenic acid, flavonoids, and alkaloids, which are effective for use on the skin as an antioxidant, anti-aging, sunscreen, moisturizer, anti-cellulite, and face brightener. The stratum corneum is the outer layer of skin that is so impenetrable that requires a formulation to help active compounds penetrate its deeper layers. The development of formulation, type, area of origin, part of the coffee used, and the extraction method affects the characteristics of obtained cosmetics.